Features of the Application of Geographic Information Systems in International Tourism (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the features of the use of information and GIS in tourism.Investigated the advantages of the introduction of information resources in the field of international tourism, the analysis of the opportunities arising from the use of information technology in the tourism industry. The international tourism market is an information-intensive and requires the use of information technology more than any other field of activity. The separate sphere of relationsconstitutes a network of information technology that integrates business entities one industry and stimulates the use of information resources of the whole society. GIS is based on systemic relations arising between business entities in various regions of the country. Special attention is focused on the assessment of tourist activity of Ukraine, the use of computer networks in the enterprise. The public policy should be based on the analysis of the tourism industry and itsposition in international markets. Enterprises tourism industry can use geographic information systems and tourist information system as a statistical system for research, modeling and planning of its activities.
Keywords: information, information technology, tourism sector, geographic information system, international tourism.